Dual phenomenon of surface plasmon and laser optics induced EM enhancement for rapid DNA detection with semiconductor nanostructures (SiNWs/AgNPs). Issue 1 (1st August 2022) - Ramachandran, Krithikadevi; Dauodi, Kais; Columbus, Soumya; Tlili, Abdelaziz; Gaidi, Mounir
Abstract: Recently exploring bioanalytical instrumentation principles emphasized with combination of optics and EM fields in surface enhanced Raman spectroscopy (SERS). The principles favour the rapid detection of DNA with proper fabrication of SERS sensor. 1D semiconductor nanostructures (SiNWs) functionalization with plasmonic silver nanoparticles are fabricated by PLD process and exploited for SERS detection of DNA. The DNA nucleotide bands are indexed with reference to their Raman shift as Adenine (A), Guanine (G), Cytosine (C), Thymine (T) at Raman spectral regions of 1352 cm -1, 676 cm -1, 1625 cm -1, 1441 cm -1 respectively. The finest conditions for sensitive detection of DNA were investigated and their interaction mechanism are presented. The point-to-point reproducibility measurements imprinted higher degree of concordancy. The designed SERS sensor will be definitely helpful almost in all application fields with portable handheld Raman spectrophotometer in near future.